2019
DOI: 10.31967/relasi.v15i2.311
|View full text |Cite
|
Sign up to set email alerts
|

The Effects Of Endorser Credibility, Attitude Toward To ADS, And Brand Attitude On Purchase Intention

Abstract: Development of motorcycle industry in Indonesian was represent by four producer’ from Japan, such Honda, Suzuki, Yamaha, and Kawasaki. Each brand was known by society, but how would people perceived it. How celebrity endorsements affect consumer purchase decisions is studied extensively by marketing and social psychology researchers. This research will measure endorser credibility of one of motorcycle brand. This research also conducts to discuss the impact of endorser credibility on attitude toward to ad and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 11 publications
0
4
1
5
Order By: Relevance
“…The results of the hypothesis test explain that credibility on repurchase intention is 0.744 > 0.05 with an original sample value of 0.057, so the conclusion that can be drawn is that H8 is not supported by data or there is no influence between endorser credibility on repurchase intention. The results of this hypothesis testing are different from previous studies which revealed that the number of repurchases is shaped by customer attitudes towards endorser credibility (Darmawan et al, 2019).…”
Section: Hypothesis Testingcontrasting
confidence: 99%
See 1 more Smart Citation
“…The results of the hypothesis test explain that credibility on repurchase intention is 0.744 > 0.05 with an original sample value of 0.057, so the conclusion that can be drawn is that H8 is not supported by data or there is no influence between endorser credibility on repurchase intention. The results of this hypothesis testing are different from previous studies which revealed that the number of repurchases is shaped by customer attitudes towards endorser credibility (Darmawan et al, 2019).…”
Section: Hypothesis Testingcontrasting
confidence: 99%
“…Endorsers who have trusted credibility will represent the advertised brand. Products that are advertised appropriately will form a good brand perception in consumers (Darmawan et al, 2019). Endorser credibility is explained as someone who is considered an expert in communicating messages, honest and trustworthy in providing objective opinions on a product (Sab'ah et al, 2022).…”
Section: Endorser Credibilitymentioning
confidence: 99%
“…The influence of attitude toward sector and sector reputation on purchasing stock intention Previous research has consistently supported the relationship between attitude and purchase intention in various contexts (Fishbein and Ajzen, 1975;Darmawan et al, 2019;Quoquab et al, 2017;Tran and Nguyen, 2022;Jaiswal and Kant, 2018). In the context of investment decisions, brand attitude has been found to affect the choice of one brand over another (Ali, 2011;Md Husin et al, 2022;Çal and Lambkin, 2017a, b).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 95%
“…Perusahaan yakult berusaha untuk dapat meningkatkan niat beli konsumen agar dapat memperkuat keunggulan bersainga atau bertahan pada persaingan bisnis (Darmawan & Grenier, 2021). Niat beli merupakan perasaan pada konsumen untuk menggunakan produk akibat adanya ketertarikan pada sebuah produk (Darmawan et al, 2019;. Niat beli tinggi dapat diukur dengan jumlah besar yang diinginkan oleh konsumen .…”
Section: Pendahuluanunclassified